MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia